MOLECULAR CYTOGENETIC REVIEW OF COMPLETE HYDATIDIFORM MOLE - Mahendra, Agung Nova (Medicina; Vol 43 No 1 (2012): Januari 2012)
Complete Hydatidiform Mole (CHM) is a pathologic pregnancy characterized by placental development regulatory genes defect. CHM is of significant importance to be characterized because of its relatively high potential to become malignant. Misdiagnosis is relatively common when histological method or cell ploidy determination is used as diagnostic tool. Knowledge of CHM genesis and genetic constitution serves as a basis to establish accurate diagnosis, and this can be achieved through the use of molecular cytogenetical approaches. This article is aimed on giving deeper understanding of CHM genesis from the perspective of molecular cytogenetics. By using molecular cytogenetical characterization, researchers found 2 CHM variants, namely BiCHM ( Biparentally-inherited CHM) and AnCHM ( Androgenetic CHM) with complex genetic heterogeneity. These findings also contribute to the improvement of molecular diagnostics, chemotherapeutics, genetic counselling, and gene therapy. (MEDICINA 2012;43:41-45).
Keywords: CHM, genesis, molecular cytogenetics